2011
DOI: 10.1093/bja/aeq416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous lidocaine on myocardial injury after off-pump coronary artery surgery

Abstract: Continuous i.v. infusion of lidocaine during surgery reduces myocardial injury in patients undergoing OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
(17 reference statements)
0
19
0
2
Order By: Relevance
“…In most recent years several systematic reviews of the use of perioperative IVLI for pain have been published, including a Cochrane review in which 45 randomized controlled trials with a total of 2802 participants were thoroughly analyzed . Among all these trials, however, only a handful of studies included ICU patients and attempted to assess ICU‐related outcomes . Furthermore, ICU patients with organ dysfunctions such as decreased cardiac output, kidney dysfunction, or hepatic impairment were not examined in detail in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In most recent years several systematic reviews of the use of perioperative IVLI for pain have been published, including a Cochrane review in which 45 randomized controlled trials with a total of 2802 participants were thoroughly analyzed . Among all these trials, however, only a handful of studies included ICU patients and attempted to assess ICU‐related outcomes . Furthermore, ICU patients with organ dysfunctions such as decreased cardiac output, kidney dysfunction, or hepatic impairment were not examined in detail in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The lidocaine infusion was terminated either at skin closure or the end of the surgical procedure [45,186,188,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206]; 1 h after surgery/skin closure [207][208][209][210][211][212]; 1 h after arrival in the post anaesthesia care unit (PACU) [213]; 4 h post-operatively [214]; up to 8 h post-operatively (or at PACU discharge whichever occurred earlier) [187]; after a total of 12 h [215]; 24 h post-operatively [216][217][218][219][220][221][222][223]; 48 h post-operatively [215,[224][225][226]; or on the day of return of bowel function or, at the latest, on the fifth post-operative day [189]. One study did not report the cessation time for the lidocaine infusion [227].…”
Section: Role Of Ivlt In Acute Perioperative Painmentioning
confidence: 99%
“…Some studies have suggested that using inhalational anesthetic agents for OPCAB might decrease myocardial injury and accelerate recovery of myocardial contractility (49,50). On the other hand, many different types of total intravenous (IV) anesthesia medication, including propofol, have been utilized for OPCAB surgery (48,(51)(52)(53). Lee and his associates (51) demonstrated that continuous IV infusion of lidocaine during OP-CAB surgery could reduce myocardial injury.…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%